Acute serous meningitis in a patient with erythema infectiosum - Čanović Predrag; Ravić-Nikolić Ana (Vojnosanitetski Pregled)
Bacground. Clinical manifestations caused by parvovirus B19 (PVB19) are various and depend on the age and immunity of an infected person. In children, the most frequent clinical manifestation of parvovirus B19 primary infection is erythema infectiosum (EI). Case report. In this case report we presented a 12-year-old patient with 2 clinical syndromes: erythema infectiosum and serous meningitis. Erythema infectiosum was manifested as fever, typical skin lesions (“slapped cheeks”), erythematous macules and papules confluent with reticular appearance on the extremities and the trunk. Serous meningitis had a mild course with an increased number of lymphocytes (120/ mm³) and the mildly increased level of proteins (0.75 g/l). The serological examination showed the presence of IgM and IgG antibodies against parvovirus B19 in serum, as well as in cerebrospinal fluid (CSF). The reduction of serum/CSF ratio of IgG antibodies was present. The symptomatic therapy was used in the treatment. The course and the prognosis were benign. Conclusion. Human PVB19, although non-specifically associated with CNS diseases could be an etiological factor that might cause serous meningitis. So, it should be considered in different diagnosis in patients with aseptic meningitis, especially during the outbreaks of erythema infectiosum.